A comparative study of ultrasonic cavitation and Fenton's reagent for bisphenol A degradation in deionised and natural waters - Abdelmalek, Fatiha; Torres, RA; Combet, E; Pétrier, C; Pulgarin, C (Journal of Hazardous Materials, 2007)
Bisphenol A (BPA), a xenobiotic that exhibits endocrine disrupting action can be found in surface water. Its complete elimination can beobtained by advanced oxidation processes, notably upon the application of ultrasonic waves. In order to evaluate the feature of ultrasound relevanceand the involvement of the hydroxyl radical in the BPA sonochemical degradation, ultrasound action was compared to Fenton’s reaction in thecases of deionised acidic water (pH 3) and natural water (pH 7.6, main ions concentration: Ca2+= 486 mg L−1,Na+= 9.1 mg L−1,Cl−=10mgL−1,SO42−= 1187 mg L−1, HCO3−= 402 mg L−1). Ultrasound was performed at 300 kHz and 80 W. Fenton’s process was operated using ferroussulphate (100 mol L−1) and continuous H2O2addition at the rate as it is produced when sonication is applied in water in absence of substrate.Experiments carried out in deionised water show that both processes exhibit identical BPA elimination rate and identical primary intermediates.Main chemical pathways involve reactions with•OH radical. Chemical oxygen demand (COD) and total organic carbon (TOC) analyses showthat the Fenton’s process is slightly more efficient than ultrasonic treatment for the removal of BPA by-products in the case of deionised water.Experiments conducted in natural water evidenced the inhibition of the Fenton process while the ultrasound action was not hampered.© 2007 Elsevier B.V. All rights reserved.
Keywords: Endocrine disrupting chemical; Bisphenol A elimination; Sonochemical degradation; Fenton’s reagent; Water treatment; Advanced oxidation